Understanding community engagement from practice: a phenomenographic approach to engineering projects - Acero, Andres; Ramirez-Cajiao, Maria Catalina; Baillie, Caroline (Frontiers in Education, 2024)
Introduction Engineering professors involved in community projects strive to enhance engagement through a combination of social sciences and engineering methodologies. Recognizing the growing importance of critical methodologies, particularly those rooted in social justice and community design, researchers have explored their impact on fostering meaningful collaborations between engineers, students, and community partners. Methods This study employs a phenomenographic approach to explore how a cohort of engineering professors, students, and community members conceptualize their participation in community-engaged practices. Results Our findings reveal a nuanced outcome space comprising five distinct ways in which individuals perceive their community engagement: as interdisciplinary endeavors, addressing community issues, engaging in co-design, and addressing systemic barriers. These conceptual frameworks elucidate a progression in the depth of engineers’ involvement with the community, underscoring the significance of systems literacy and social justice in more intricate contexts. Discussion These results advocate for engineers to adopt an active membership approach, emphasizing collaboration, when working on engineering projects within communities, as opposed to adopting passive roles that may undermine the impact of community engagement. Conclusion In conclusion, a deeper understanding of the varied conceptualizations of community engagement among engineering professors, students, and community members underscores the importance of adopting proactive roles and fostering collaborative approaches in community projects.